Proactivity during organizational entry: The role of desire for control. - Ashford, Susan J.; Black, J. Stewart (Journal of Applied Psychology, 1996)
This study described the various ways that newcomers proactively attempt to gain feelings of personal control during organizational entry and examined their longitudinal effects on self-reported performance and satisfaction in a sample of organizational newcomers. The results suggest that individuals engage in proactive activities such as information and feedback seeking, relationship building, job-change negotiating, and positive framing during entry and that individual differences in desired control were related to 6 proactive entry tactics. However, only some of these tactics were related to self-reported performance and job satisfaction. The socialization literature describes the ways in which organizations mold and shape individual behavior (Van Maanen & Schein, 1979). The literature has focused on stages of socialization and on situational factors that influence individuals during the entry period (Reichers, 1987). More recently, researchers have begun to examine the role that individual dispositions might play in the en